2020
DOI: 10.15562/ism.v11i1.623
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis as early detection of diabetes mellitus: a literature review

Abstract: Background: Diabetes mellitus (DM) is a growing health problem and its prevalence is dramatically increasing, particularly in Indonesia. It can affect every organ in the body, and one of the oral manifestations is periodontitis characterized by the loss of tissue attachment. This review aims to identify further the periodontitis as early detection of diabetes mellitusMethods: A review of relevant literature was performed to elaborate on periodontitis involvement in diabetes mellitus. A total of 25 qualified pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…It was reported that periodontal infection can impair glycemic control by increasing tissue insulin resistance. 4,7 The results of this study revealed that bone morphogenetic protein-2 (BMP-2) levels in the periodontitis group with type 2 DM were significantly lower compared to the BMP-2 levels in the periodontitis group without type 2 DM. This may indicate that type 2 DM was likely to trigger more severe periodontal tissue damage.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…It was reported that periodontal infection can impair glycemic control by increasing tissue insulin resistance. 4,7 The results of this study revealed that bone morphogenetic protein-2 (BMP-2) levels in the periodontitis group with type 2 DM were significantly lower compared to the BMP-2 levels in the periodontitis group without type 2 DM. This may indicate that type 2 DM was likely to trigger more severe periodontal tissue damage.…”
Section: Discussionmentioning
confidence: 85%
“…Diabetic microangiopathy, impaired immune response, and lower resistance to infection may contribute to the development of periodontitis in uncontrolled diabetics. 4 Hyperglycemia can cause indirect damage through the end result of glucose products, that is advanced glycation end products (AGEs) mediated by RANKL, and direct cell damage from stimulation of intracellular pathways. Advanced glycation end products (AGEs) cause an increase in matrix metalloproteinases (MMPs) and a decrease in collagen synthesis resulting in collagen degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations